“Slow” Cesarean Section by Inconsistent Corporal Scar (Clinical Case) - R. I. Safiullin; I. I. Musin; A. R. Molokanova (Креативная хирургия и онкология, 2018)
Introduction. Increasing the initial number of caesarean delivery operations involves certain risks when planning and carrying subsequent pregnancies. Despite the trend towards operative childbirth being gradually being replaced by natural, the frequency of recurrent caesarean is higher than the prevailing rate due to scar inconsistency and the presence of a “classic” (corporal) scar on the uterus. The use of corporal access to date is gradually being replaced by less traumatic access. The operation of “slow” caesarean section is considered as an alternative approach to surgical delivery.Purpose and objectives. To analyse the operation of “slow” caesarean section in the presence of corporal scars on the uterus.Materials and methods. The resulted clinical case of incomplete rupture of the uterus by corporal scar in the second pregnancy at a period of 38 weeks. Corporal scarring as a result of caesarean operations in the case of interruption of first pregnancy at a period of 22–23 weeks.Results. The patient was discharged in a satisfactory condition on the 5th day with the child. Postoperative period without complications; results of analyses performed prior to discharge within normal limits.Discussion. The conducted corporal incision at the first pregnancy was inexpedient due to presenting increased risks in subsequent pregnancies. For the termination of pregnancy in the second trimester, it was necessary to consider therapeutic methods, the operations of a minor caesarean section or a caesarean section in the lower segment of the uterus.Conclusion. Conducting “slow” caesarean section has the following advantages over classic caesarean section: soft adaptation of the foetus to environmental conditions, purification of the mucous oropharynx of the foetus, establishing a stronger bond between the mother and her future child. In future, we plan to conduct a clinical evaluation of children delivered through a “slow” caesarean section.